2011
DOI: 10.1159/000332805
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Key Virulence Proteases Bace16 and Bae16 in <i>Bacillus nematocida</i> B16 to Improve Its Nematocidal Activity

Abstract: Proteases Bace16 and Bae16, an alkaline serine protease and a neutral protease, respectively, in the nematocidal bacterium Bacillus nematocida B16, have been identified as two key virulence factors and shown to have remarkable nematotoxic activities against the free-living nematode Panagrellus redivius and the plant parasite nematode Bursaphelenchus xylophilus. To facilitate the successful biological control application of this organism in the field, we genetically altered the strain B. nematocida B16 and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…To delete the targeted genes in B. amyloliquefaciens SQR9, 1-kb fragments located upstream and downstream of the target gene were amplified. The 1.6-kb erythromycin resistance gene (Em r ) was amplified from plasmid pAX01 (51), which partially overlapped the upstream and downstream fragments of each target gene. The upstream and downstream fragments were fused with the erythromycin resistance gene by overlap extension.…”
Section: Methodsmentioning
confidence: 99%
“…To delete the targeted genes in B. amyloliquefaciens SQR9, 1-kb fragments located upstream and downstream of the target gene were amplified. The 1.6-kb erythromycin resistance gene (Em r ) was amplified from plasmid pAX01 (51), which partially overlapped the upstream and downstream fragments of each target gene. The upstream and downstream fragments were fused with the erythromycin resistance gene by overlap extension.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the nematicidal virulence factors in B. firmus strain DS-1, we sequenced the genome of B. firmus DS-1 (accession number APVL00000000) with Illumina sequencing technology by BGI Shenzhen 24 . Using the reported nematicidal virulence-associated genes, including Bace16 of Bacillus nematocida 10 , Bmp1 from Bacillus thuringiensis 25 , and all other proteases mentioned in Bmp1 research 25 , as well as the hemolysin superfamily proteins, peptidase_S8, peptidase_M6, peptidase_M7, and peptidase_M48 superfamily proteins, a whole genome InterproScan analysis of the B. firmus DS-1 genome was conducted, and the results showed that the B. firmus DS-1 genome harbors multiple potential extracellular protease genes in the genome ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because Sep1 has similar conserved domains and enzymatic characteristics as the reported extracellular proteases from nematicidal bacteria 10 32 and nematode-trapping fungi 26 27 28 , there is a possibility that Sep1 is an extracellular protease that can destroy the nematode physical barrier. To confirm this hypothesis, we then investigated whether the Sep1 protein degraded tissues from the nematodes C. elegans and M. incognita .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations